Russian emigrant press about the border conflict on Damansky Island in 1969 - T. S. Kulepanova-Shugaylo (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the perception of the Sino-Soviet conflict on Damansky Island in 1969, as well as international relations between the USSR and China during this period by representatives of the Russian diaspora. The indicated issue has not received due coverage in historiography. The authors have analyzed publications of major émigré press of various political colors published in the 20th century on different continents. The theoretical basis of the study is a combination of the institutional approach and the problematic method. The analysis of these sources made it possible to identify a wide range of opinions on the developing Sino-Soviet conflict among supporters of different socio-political views in the Russian diaspora — monarchists, liberal democrats and pro-Soviet émigrés. Anti-communists of the Russian diaspora viewed the foreign policy of the USSR through the prism of anti-Soviet ideology. Representatives of the White émigré community adhered to imperial views and called on the USSR leadership to preserve the territorial unity of the country. Position of the pro-Soviet newspaper «Russky Golos» stood out, advocating for the resumption of friendship between the USSR and the China.